Экономическая часть ВКР для технических специальностей: электронный курс - Тухватулина Л. Р. Лилия Равильевна; Видяев И. Г. Игорь Геннадьевич; Чистякова Н. О. Наталья Олеговна; Гаврикова Н. А. Надежда Александровна (Томск, TPU Moodle, 2015)
Заглавие с экрана